In vitro analysis of shear bond strength and adhesive remnant index of different metal brackets - Fernanda de Souza Henkin; Érika de Oliveira Dias de Macêdo; Karoline da Silva Santos; Marília Schwarzbach; Susana Maria Werner Samuel; Karina Santos Mundstock
ABSTRACT Introduction: There is a great variety of orthodontic brackets in the Brazilian market, and constantly evaluating them is critical for professionals to know their properties, so as to be able to choose which product best suits their clinical practice. Objectives: To evaluate the bond strength and the adhesive remnant index (ARI) of different brands of metal brackets. Material and Methods: A total of 105 bovine incisors were used, and brackets of different brands were bonded to teeth. Seven different bracket brands were tested (MorelliTM, American OrthodonticsTM, TP OrthodonticsTM, Abzil-3MTM, OrthometricTM, TecnidentTM and UNIDENTM). Twenty-four hours after bonding, shear bond strength test was performed; and after debonding, the ARI was determined by using an optical microscope at a 10-fold increase. Results: Mean shear bond strength values ranged from 3.845 ± 3.997 (MorelliTM) to 9.871 ± 5.106 MPa (TecnidentTM). The majority of the ARI index scores was 0 and 1. Conclusion: Among the evaluated brackets, the one with the lowest mean shear bond strength values was MorelliTM. General evaluation of groups indicated that a greater number of bond failure occurred at the enamel/adhesive interface.